Guided inquiry based worksheet development to improve science process skills in junior high school students - I F Qary; M N Soetjipto (International Conference on Mathematics and Science Education of Universitas Pendidikan Indonesia, 2018)
This development research aims to produce a suitable (valid, practical, and effective) guided inquiry based-worksheet in the topic of energy to drill student science process skills. This research is developed using three stages of 4D (four D models) which consists of define, design, and develop. The developed worksheet is tested to 12 students of grade VII SMPN 5 Pamekasan. The data collection uses validation method, observation, test, and questionnaire. The data analysis technique applies qualitative descriptive analysis. The research result shows that: 1) the developed worksheet is categorized valid, 2) the worksheet practicality seen from the lesson plan implementation using guided inquiry model is categorized good, 3) the worksheet effectivity seen from the N-gain score, student science process skills is categorized high and the student response to the worksheet is considerably positive. Based on the research result, it can be concluded that the developed worksheet is valid, practical, and effective to improve student science process skills.